Living conditions and reproductive installation of women living in the cities of Irkutsk region - A. V. Boyeva; Ya. A. Leshchenko; M. V. Kuleshova (Acta Biomedica Scientifica)
According to the survey the effect of the conditions of family life on the reproductive behavior of women was studied, as well as the comparative characteristic of matrimonial and reproductive orientations of women with children and women without children (female students) living in the cities of Irkutsk region. The dependence between the housing and the material conditions of the family and the number of children ever born was determined: the average number of children born by women from families with their own housing and living separately from other relatives were higher, average number of children from women from families with rather high income was lower than from ones who considered theirfamilies to have low and extremely low income. Reproductive intentions the two-child and one-child women give birth to another baby hampers the availability of material and housing problems. The average number of children was higher in women with secondary special education, employees in private enterprises and workers in large industrial enterprises. Achieving success in family life is a factor for the well-being for the majority of women with children, and does not depend on the number of children. For the girls, along with success in family life the opportunity to "power over people" is also important. The fact of having children does not affect the formation of marital and family systems: both categories of respondents are not sufficiently developed to implement the installation of household functions of the family and the low importance of sexual relations in marriage, they are more focused on achieving social viability and prone to egalitarianism. The girls have more developed focus on the educational function of children than women. Indicators ideal medium, the expected and desired number of children in two and three-child women is higher than the ones in single-child women and girls who do not have children.